2015
DOI: 10.1186/s12876-015-0353-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in upper gastrointestinal diagnosis over four decades in Lusaka, Zambia: a retrospective analysis of endoscopic findings

Abstract: Background and aimsThere a shortage of robust information about profiles of gastrointestinal disease in sub-Saharan Africa. The endoscopy unit of the University Teaching Hospital in Lusaka has been running without interruption since 1977 and this 38-year record is largely intact. We report an analysis of endoscopic findings over this period.MethodsWritten endoscopy records from 29th September 1977 to 16th December 2014 were recovered, computerised, coded by two experienced endoscopists and analysed. Temporal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Portal hypertension secondary to schistosomal fibrosis is still common in Kenya complicating into upper GI bleeding (9). Kayamba et al in a study on trends of upper GI endoscopy in Zambia, showed that Esophageal varices were the commonest finding in patients presenting with haematemesis, increasing by 14 % per decade in that patient group (19) Evolution from injection sclerotherapy to endoscopic variceal ligation is portrayed in our findings as well as other studies (12,20). All patients with esophageal varices underwent variceal band ligation.…”
Section: Discussionsupporting
confidence: 77%
“…Portal hypertension secondary to schistosomal fibrosis is still common in Kenya complicating into upper GI bleeding (9). Kayamba et al in a study on trends of upper GI endoscopy in Zambia, showed that Esophageal varices were the commonest finding in patients presenting with haematemesis, increasing by 14 % per decade in that patient group (19) Evolution from injection sclerotherapy to endoscopic variceal ligation is portrayed in our findings as well as other studies (12,20). All patients with esophageal varices underwent variceal band ligation.…”
Section: Discussionsupporting
confidence: 77%
“…Peptic ulcer disease and erosions due to Helicobacter pylori infection and NSAID use are common causes of GI bleeding worldwide [1,6,10,12,18,[21][22][23][24][25]. Bleeding from gastro-oesophageal varices due to liver cirrhosis is an increasing cause of bleeding in the West, but is also a major cause in parts of South America, Asia, Africa and the Middle East where there is high prevalence of hepatitis or schistosomiasis [26][27][28][29][30][31][32][33]. Symptoms of GI bleeding include hematemesis and coffee grounds vomitus, melaena and the passage of fresh red blood in the stool, and clinical signs of shock such as hypotension and tachycardia.…”
Section: Introductionmentioning
confidence: 99%
“…Peptic ulcer disease and erosions due to Helicobacter pylori infection and non-steroidal antiinflammatory drug (NSAID) use are common causes of GI bleeding worldwide [1,6,10,12,18,[21][22][23][24][25]. Bleeding from gastro-oesophageal varices due to liver cirrhosis is an increasing cause of bleeding in the West, but is also a major cause in parts of South America, Asia, Africa and the Middle East where there is high prevalence of hepatitis or schistosomiasis [26][27][28][29][30][31][32][33]. Symptoms of GI bleeding include haematemesis and coffee ground vomitus, melaena and the passage of fresh red blood in the stool, and clinical signs of shock such as hypotension and tachycardia.…”
Section: Introductionmentioning
confidence: 99%